2020
DOI: 10.1186/s13006-020-00300-0
|View full text |Cite
|
Sign up to set email alerts
|

Examining working mothers’ experience of exclusive breastfeeding in Ghana

Abstract: Background: Although substantial evidence exists on factors that influence exclusive breastfeeding, there is a general lack of qualitative studies that examine how specific workplace factors constrain or promote exclusive breastfeeding among working mothers. The current study therefore examines working mothers' experience of exclusive breastfeeding, laying emphasis on the influence of workplace factors on working mothers' decision to exclusively breastfeed their babies. Methods: The study uses a qualitative re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
1
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 26 publications
3
56
1
11
Order By: Relevance
“…Bu nedenle emzirmenin erken bırakılabildiği, ilk altı ay sadece anne sütü verme durumu ile emzirmenin başlatılmasının da risk altında olduğu ifade edilmektedir. 24 Bu kapsamda çalışan kadınlarda emzirmenin başlatılması ve sürdürülmesiyle ilişkili faktörlerin belirlenmesini amaçlayan bu çalışmanın bulguları ilgili literatür doğrultusunda tartışılmıştır.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Bu nedenle emzirmenin erken bırakılabildiği, ilk altı ay sadece anne sütü verme durumu ile emzirmenin başlatılmasının da risk altında olduğu ifade edilmektedir. 24 Bu kapsamda çalışan kadınlarda emzirmenin başlatılması ve sürdürülmesiyle ilişkili faktörlerin belirlenmesini amaçlayan bu çalışmanın bulguları ilgili literatür doğrultusunda tartışılmıştır.…”
Section: Discussionunclassified
“…Çalışan anneler için emzirmeyi etkileyen sorunlar arasında esnek olmayan bir çalışma programı, işe erken dönme, kısa doğum izni, mahremiyet eksikliği, izlenme ve yargılama duyguları, yorgunluk ve iş yerinde destek eksikliği bulunmaktadır. 24 Çalışmamızda, işe başladıktan sonra emzirmenin devam ettirilmesinde ücretli doğum izninin sağlanması, çalışma arkadaşlarının desteği, eş desteği ve emzirme tecrübesinin etkili olduğu saptanmıştır. Ancak sosyo-demografik özellikler, diğer emzirmeyi destekleyici iş yeri koşulları ile işe başladıktan sonra emzirmeye devam etme arasında anlamlı bir ilişki bulunmamıştır.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Recent studies have also investigated the lived experiences and views of breastfeeding mothers in paid work and tertiary institutions and have identi ed some individual and organizational-level factors that affect optimal breastfeeding practice. Abekah-Nkrumah and colleagues [12], found factors such as lack of knowledge and understanding of exclusive breastfeeding, negative lived experiences of working mothers, and unsupportive organizational environment to affect exclusive breastfeeding. A study of institutional-level support for breastfeeding among tertiary students also found a stern con ict between breastfeeding and academic work due to lack of breastfeeding support for student-mothers.…”
Section: Work Breastfeeding and Workplace Support In Ghanamentioning
confidence: 99%
“…Assessing breastfeeding support in healthcare facilities at the Effutu Municipality would illuminate further our understanding of organizational-level factors that impede breastfeeding practice in Ghana. Several theoretical and conceptual frameworks, including the maternal role-incompatibility hypothesis [15], social-ecological theory [12]; work-family con ict framework [16] have been used in studies on work-childcare con ict. This study is predicated on the Social Support Theory (SST).…”
Section: Theoretical Frameworkmentioning
confidence: 99%